Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007223
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatments for incomplete miscarriage (less than 24 weeks)

Abstract: Background-Miscarriage occurs in 10% to 15% of pregnancies. The traditional treatment, after miscarriage, has been to perform surgery to remove any remaining pregnancy tissues in the uterus. However, it has been suggested that drug-based medical treatments, or expectant care (no treatment), may also be effective, safe and acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
2
2
0
2
Order By: Relevance
“…This study, as has been observed in another study, demonstrated higher cases of pyrexia, nausea and chills among the misoprostol versus the MVA group 19. These symptoms are common side effects of misoprostol, with pyrexia being the most common side effect as a result of the drug’s action (prostaglandin E1 analogue) on the central thermoregulatory centre 22.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study, as has been observed in another study, demonstrated higher cases of pyrexia, nausea and chills among the misoprostol versus the MVA group 19. These symptoms are common side effects of misoprostol, with pyrexia being the most common side effect as a result of the drug’s action (prostaglandin E1 analogue) on the central thermoregulatory centre 22.…”
Section: Discussionsupporting
confidence: 83%
“…The success rate of 600 μg oral misoprostol in this study was comparable with findings from varying dosages and routes of administration of misoprostol used in other studies 8,17,18. Similarly, a recent Cochrane Database Systematic Review that compared different routes of administration of misoprostol with MVA showed no clear evidence to suggest that one regimen was superior to another 19. Contrary to this and other findings, Weeks et al .’s study in Uganda found a slightly higher success rate among the misoprostol group than the MVA group, although the difference was not statistically significant (96.3% versus 91.5%; P = 0.43) 13.…”
Section: Discussionsupporting
confidence: 82%
“…El aborto espontáneo e incompleto es una grave preocupación de salud pública, ocurre en 10 a 15% de los embarazos (40) y su falta de tratamiento adecuado puede provocar alta morbilidad e incluso la muerte. El principal peligro del aborto incompleto no infectado es el shock hipovolémico (41) .…”
Section: Resultsunclassified
“…El principal peligro del aborto incompleto no infectado es el shock hipovolémico (41) . Existen diferentes formas de resolver el aborto incompleto mediante métodos quirúrgicos, dentro de los cuales la regla de oro hasta ahora viene siendo la aspiración manual endouterina (42) ; sin embargo, es evidente que el tratamiento médico mediante el uso del misoprostol viene ganando cada vez más terreno y se ha convertido en una opción importante para tal fin, no solo en los embarazos de 12 semanas o menos, sino también en aquellos menores de 22 semanas, lo que libera a la mujer de una intervención quirúrgica y el manejo se hace ambulatoriamente, con el valor agregado de un costo menor (40,(43)(44)(45) . Así mismo, el misoprostol ha sido demostrado como medicamento muy eficaz en el tratamiento del aborto fallido o retenido (46,47) .…”
Section: Resultsunclassified
“…17 The available Cochrane systematic review evidence suggest that expectant care as well as medical treatment with Misoprostol are acceptable alternatives to routine vaginal surgical evacuation. 18 Despite the fact that so many studies prove the benefits of medical treatment, the services go unreached to many strata of population owing to the widespread illiteracy and the unmet availability of resources and trained personnel, that many are lost for follow-up as well as availability of Misoprostol over-the-counter in our country has led to misuse of this wonder drug. Limitations This study was done on a small and restricted population group.…”
Section: Discussionmentioning
confidence: 99%